3D printed hydrogel electronic devices manufacturing method and conductive materials
The preparation of hydrogel electronic devices through 3D printing technology solved the problems of low process complexity and accuracy in the existing methods, achieved high-precision and high-designability hydrogel electronic devices, and overcome the stretching of conductor materials Constrained, demonstrates excellent conductivity and strain responsiveness.
Patent Information
- Application Number
- CN202111358090.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-11-16
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2041-11-16
AI Technical Summary
The preparation methods of existing hydrogel electronic devices are cumbersome, with low precision, insufficient design and spatial freedom, and the conductor materials used are limited in tensile degree and have a risk of leakage.
Hydrogel electronic devices are prepared by using 3D printing technology to form microgel particles by coordinating bond crosslinking ionically crosslinkable polymer compounds, radically polymerizable monomers, crosslinking agents and metal ions in deionized water , and mixed with aqueous polyvinylpyrrolidone solution and micron silver sheets to form conductive ink that can be used for 3D printing, printed in molds with a 3D printer and cured under ultraviolet light or heating conditions.
It realizes the preparation of hydrogel electronic devices with high precision, high design and high degree of freedom, overcomes the process complexity and tensile limitations of conductor materials in traditional methods, has excellent conductivity and strain response, and is suitable for Wearing devices and healthcare fields.
Smart Images

Figure HDA0003358051800000011 
Figure HDA0003358051800000012 
Figure HDA0003358051800000021
Abstract
Description
Technical Field
[0001] The present invention relates to the field of flexible electronic device processing, and in particular to a manufacturing method and conductive material for a 3D printed hydrogel electronic device. Background Art
[0002] Flexible electronic devices have attracted more and more attention and research due to their attractive prospects in biological detection and treatment, neuroscience research, and wearable electronic devices. They are expected to replace traditional rigid electronic devices through technological breakthroughs in the future and achieve industry innovation. As a new type of material that has recently emerged, hydrogel electronic devices have natural biocompatibility, low toxicity, high water content, easy chemical modification, ion diffusion, and similar mechanical properties to biological tissues, thus showing good development prospects.
[0003] Hydrogel electronic devices are still in the early stages of development. The methods used to prepare hydrogel electronic devices reported in the literature, such as the molding method, laser etching method, and flow channel method, generally have the disadvantages of complicated preparation process, too much manual operation, low precision, low designability, and low three-dimensional spatial freedom, and cannot be promoted as standardized methods. In addition, the main conductor materials currently used in hydrogel electronic devices, including (snake-shaped) metal wires and liquid metals, also have problems such as limited stretchability and leakage risks.
[0004] CN110970232A discloses a stretchable microelectronic device based on a hydrogel and a preparation method thereof. The device is composed of a hydrogel substrate with ion conductivity and a stretchable patterned microelectrode on the surface. The preparation process includes obtaining an intermediate product with a preset electrode pattern, pre-stretching the tough hydrogel and fitting it with the intermediate product to achieve electrode pattern transfer, and slowly releasing the hydrogel to restore it to an unstretched state, thereby obtaining a hydrogel electronic device with good stretchability and a certain precision (line width 400 μm); the invention patent is prepared by a transfer method, but because the transfer method can only attach the circuit to the surface of the hydrogel, it is difficult to obtain a hydrogel electronic device with a 3D structure and more complex functions, such as a hydrogel-based solenoid antenna, and there are many restrictions on the electrode materials that can be selected. Furthermore, the transfer method requires the manufacture of a corresponding mask plate in advance, and the transfer is performed after the electrode pattern is printed on the intermediate material. The process is cumbersome and there are many manual operations. Summary of the invention
[0005] In view of the above-mentioned deficiencies in the prior art, the present invention aims to provide a method for manufacturing 3D printed hydrogel electronic devices and conductive materials, thereby providing feasibility for more easily preparing hydrogel electronic devices with high precision, designability and freedom.
[0006] In order to achieve the purpose of the present invention, in a first aspect, the present invention provides a hydrogel matrix material, wherein the hydrogel matrix material is obtained by dissolving an ionically crosslinkable polymer compound (an ionically crosslinked polymer conforming to an orthogonal curing mechanism), a free radical polymerizable monomer, a crosslinking agent and an initiator in deionized water, then introducing metal ions (preferably calcium ions) to allow the polymer compound to undergo ion crosslinking through coordination bonds, and breaking the resulting gel into micronized gel particles;
[0007] Wherein, the initiator is a thermal initiator or a photoinitiator.
[0008] Furthermore, the ion-crosslinkable polymer compound can be selected from sodium alginate, chitosan, hyaluronic acid, etc., preferably sodium alginate.
[0009] Furthermore, the free radical polymerizable monomer may be selected from acrylamide, polyethylene glycol diacrylate (PEGDA), etc., preferably acrylamide.
[0010] Furthermore, the cross-linking agent may be a water-soluble small molecule containing two C=C bonds, preferably N,N-methylene acrylamide.
[0011] Preferably, the initiator is ammonium persulfate (APS), other water-soluble thermal initiators can also be used in the present invention.
[0012] Preferably, the photoinitiator is Igracure 2959, and other water-soluble photoinitiators can also be used in the present invention.
[0013] In a second aspect, the present invention provides a method for preparing the hydrogel matrix material, comprising the following steps:
[0014] (1) dissolving an ionically cross-linkable polymer compound and a free radical polymerizable monomer in deionized water by magnetic stirring under heating conditions to obtain a transparent viscous solution;
[0015] (2) cooling the viscous solution obtained in step (1) to below 25° C., adding a crosslinking agent, an initiator, and an ethylenediaminetetraacetic acid (EDTA) chelate of metal ions, and stirring to dissolve them;
[0016] (3) adding D-gluconolactone to the solution obtained in step (2), stirring to dissolve it, and refrigerating the resulting solution overnight to form an ion-crosslinked gel;
[0017] (4) Mechanically crushing the ion cross-linked gel obtained in step (3) into coarse gel particles, filtering the coarse gel particles into fine gel particles using a syringe and a filter, and degassing them using a planetary mixer to obtain a hydrogel matrix material that can be used for embedded 3D printing.
[0018] In a specific embodiment of the present invention, the preparation method of the hydrogel matrix material is as follows:
[0019] (1) dissolving acrylamide and sodium alginate in deionized water under heating conditions by magnetic stirring to obtain a transparent viscous solution;
[0020] (2) cooling the viscous solution obtained in step (1) to below 25° C., adding an aqueous solution of N,N-methylene acrylamide and ammonium persulfate, and then adding an aqueous solution of EDTA-CaCl2 (ethylenediaminetetraacetic acid-calcium chloride), stirring to dissolve;
[0021] (3) adding D-gluconolactone to the solution obtained in step (2), stirring to dissolve it, and refrigerating the resulting solution overnight to form a calcium alginate gel;
[0022] (4) Using a grinder, the calcium alginate gel obtained in step (3) is mechanically crushed into coarse gel particles, and then the coarse gel particles are filtered into fine gel particles using a syringe and a filter, and a planetary mixer (Thinky planetary mixer) is used to degas the particles to obtain a hydrogel matrix material that can be used for embedded 3D printing.
[0023] In the aforementioned method step (1), the mass ratio of sodium alginate, acrylamide and deionized water is (0.6-1.4):(6-10):55, wherein the proportion of sodium alginate will affect the final rheological properties of the matrix gel obtained in step (4).
[0024] In the aforementioned method step (2), the mass ratio of acrylamide, N,N-methylene acrylamide (crosslinking agent) and ammonium persulfate (thermal initiator) is 1: (0.00082-0.04): (0.01-0.05). The ratio of the crosslinking agent will affect the mechanical properties of the matrix gel after solidification into a hydrogel.
[0025] In the above method, the mass ratio of sodium alginate, 0.25M EDTA-CaCl2 aqueous solution with pH 8-9 and D-gluconolactone is 1:(1.3-3.0):(0.48-1.12).
[0026] Preferably, the pore size of the syringe and filter used in step (4) is 20-50 μm.
[0027] In a third aspect, the present invention provides a conductive material that can be used for 3D printing. The hydrogel matrix material is mixed evenly with a polyvinyl pyrrolidone aqueous solution, glycerol and micron silver flakes using a planetary mixer, and then transferred to a barrel for centrifugal degassing to obtain a conductive material that can be used for 3D printing (conductive ink that can be extruded and printed).
[0028] Preferably, the mass ratio of the hydrogel matrix material, the 40%wt polyvinyl pyrrolidone aqueous solution, glycerol and the micronized silver flakes is 1:(0.02-0.1):(0.05-0.1):(0.5-1.5). The molecular weight of polyvinyl pyrrolidone is 44000-54000Da.
[0029] Preferably, the size of the micronized silver flakes is 2-10 μm. The proportion of the micronized silver flakes can affect the conductivity of the paste after curing.
[0030] Preferably, the centrifugation conditions are: 18°C, 2000-2500g (more preferably 2500g) for 10 min.
[0031] In a fourth aspect, the present invention provides a method for manufacturing a 3D printed hydrogel electronic device, wherein the hydrogel matrix material is loaded into a mold having a certain shape, the conductive material that can be used for 3D printing is printed in the hydrogel matrix material according to a preset program using a 3D printer, and then cured under ultraviolet light or heating conditions to obtain a hydrogel electronic device with good stretchability and elasticity.
[0032] Preferably, the printing needle nozzle of the 3D printer can select an inner diameter size of 100 μm, 150 μm, 250 μm or 400 μm as needed.
[0033] Preferably, the thermal initiator is ammonium persulfate (APS), the heating temperature is 60°C, and the heating time is 1h. Curing should be carried out in a high humidity and oxygen-free environment as much as possible; the photoinitiator can be Igracure2959 with good water solubility and low toxicity, and the ultraviolet light intensity is 50mW / cm 2 , time is 1h.
[0034] The present invention provides a 3D printing manufacturing method for hydrogel electronic devices and a supporting conductive material system. The method uses calcium alginate-polyacrylamide double cross-linked network hydrogel as a substrate and utilizes its unique coordination bond-covalent bond orthogonal curing mechanism. First, alginate is cross-linked with calcium ions to form a gel, and it is mechanically broken into a micro-particle matrix that can be used as an embedded 3D printing. Because it contains acrylamide monomer, cross-linking agent and initiator inside, the matrix has the potential for subsequent covalent cross-linking and curing, and can be printed as a conductive ink after blending with micron-level silver flakes. The material system allows three-dimensional conductive structures with certain functions (such as inductance, etc.) to be freely printed in space, and can be conveniently cured and packaged through light, heat and other stimuli after printing. Compared with the currently reported hydrogel electronic device manufacturing methods, such as perfusion method, laser etching method, etc., this method has the advantages of simple process, low price, high designability, and high manufacturing freedom. The prepared hydrogel electronic device exhibits excellent conductivity, stretchability and strain responsiveness, and is expected to be applied to wearable devices, flexible robots, electronic skin and medical care.
[0035] The present invention overcomes the problems of complicated process, excessive manual operation, low precision, low spatial freedom and the like in the current preparation methods of hydrogel electronic devices, and effectively overcomes the problems of stretching limitation and seepage that may exist when using metal wires or liquid metals as wires. It has the advantages of simple and fast process, low cost, high degree of freedom, strong designability, etc., and provides a new method for the efficient preparation of hydrogel electronic devices. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 Schematic diagram of the embedded 3D method for manufacturing hydrogel electronic devices in a preferred embodiment of the present invention (a) and a photo of the solidified hydrogel electronic device (b).
[0037] Figure 2 Schematic diagram of the material principles involved in the preferred embodiments of the present invention: (a) i. Schematic diagram of matrix gel (microgel particles); ii. Schematic diagram of the chemical components of the matrix gel; (b) Schematic diagram of the conductive paste; (c) Schematic diagram of the chemical components of the cured hydrogel.
[0038] Figure 3 The viscosity-strain rate diagram (a) of the matrix gel at different mass ratios of sodium alginate and the stress-strain curve (b) of the hydrogel after curing in a preferred embodiment of the present invention respectively reflect the rheological properties of the matrix gel before curing and the mechanical properties after curing (the numbers in the figure represent the mass ratio of sodium alginate).
[0039] Figure 4The present invention shows the manufacture and testing of the hydrogel electronic strain sensor in the preferred embodiment of the present invention; wherein, (a) the design G code simulation of the hydrogel strain sensor (above) and the actual photograph (below); (b) the testing of the hydrogel strain sensor using a tensile tester; (c) the resistance change rate-strain relationship diagram of the hydrogel strain sensor; (d) the resistance change rate-strain relationship diagram of the hydrogel strain sensor under 300% strain cycle.
[0040] Figure 5 The present invention provides the manufacture and testing of the hydrogel inductor and antenna in the preferred embodiment of the present invention; wherein, (a) a G code simulation of a 5-turn spiral inductor; (b) a physical picture of a 2-5 turn spiral hydrogel inductor; (c) a comparison chart of the experimental inductance and resistance of the 2-5 turn spiral hydrogel inductor and the simulated inductance and resistance obtained by simulation using Comsol software; (d) a G code simulation of a 3-turn solenoid antenna; (e) a physical picture of a solenoid antenna-light-emitting diode hydrogel electronic device; (f) the solenoid antenna makes the light-emitting diode emit light under the condition of power supply from the transmitting coil. DETAILED DESCRIPTION
[0041] The present invention aims to address the deficiencies in the prior art and provide a more efficient 3D printing manufacturing method for hydrogel electronic devices with higher degrees of freedom and designability, which includes a hydrogel matrix material suitable for embedded 3D printing and a printable conductive ink; the manufacturing method includes embedded 3D printing and a device curing and packaging process after printing.
[0042] The present invention adopts the following technical solution:
[0043] A. Preparation of embedded 3D printed hydrogel matrix
[0044] Sodium alginate, acrylamide, crosslinker (N,N-methylene acrylamide, MBAA), and thermal initiator (ammonium persulfate, APS) are co-dissolved in deionized water, and then calcium ions are introduced to cause alginate-calcium ions to undergo ion crosslinking through coordination bonds. The crosslinked gel is mechanically crushed and passed through a syringe filter to obtain an embedded 3D printing gel matrix with certain rheological properties. Since the matrix still contains unreacted monomers, crosslinkers, and initiators, the matrix can be covalently crosslinked by heating to achieve the curing and encapsulation of electronic devices after printing ( Figure 2 , a~c).
[0045] Preferably, the mass ratio of sodium alginate: acrylamide: deionized water is 1:8:55. Among them, changing the mass ratio of sodium alginate can adjust the rheological properties of the matrix gel and its mechanical properties after curing ( Figure 3 , a and b).
[0046] Preferably, the mass ratio of acrylamide:MBAA:APS is 1:0.0082:0.03. The ratio of the cross-linking agent will affect the mechanical properties of the matrix gel after solidification into a hydrogel.
[0047] Preferably, the calcium source is introduced in a different way from the traditional method (such as adding calcium sulfate, calcium chloride, etc.), but by adding EDTA-CaCl2 solution and D-gluconolactone (GDL) solution, so that calcium ions are slowly and evenly released in the gel, thereby facilitating the formation of a uniform and transparent calcium alginate gel. Among them, the mass ratio of sodium alginate: EDTA-CaCl2 (0.25M aqueous solution, pH 8.6): GDL is 1:2.16:0.8.
[0048] Preferably, a photoinitiator (such as Igracure 2959) can be used instead of the thermal initiator APS to give the matrix gel a photocurable property.
[0049] B. Preparation of Printable Conductive Ink
[0050] The matrix gel obtained in A was mixed evenly with polyvinyl pyrrolidone (PVP), glycerol and micronized silver flakes using a planetary stirrer, and then transferred to a 3 mL cylinder for centrifugation to obtain a conductive ink that can be extruded and printed.
[0051] Preferably, the mass ratio of 3D printed hydrogel matrix: PVP (molecular weight 44000-54000Da, 40% wt aqueous solution): glycerol: micron silver flakes is 1: 0.05: 0.05: 0.5-1.5, wherein the mass ratio of the silver flakes can affect the rheological properties of the ink and the conductivity after curing, and the size of the micron silver flakes is 5 μm.
[0052] Preferably, the centrifugation conditions are: 18°C, 2000-2500g for 10 min.
[0053] C. Printing of Hydrogel Electronics
[0054] After degassing, the embedded 3D printing matrix of A is loaded into a mold with a suitable shape, and the conductive ink of B is printed in the matrix according to the program using a direct writing 3D printer (mainly including three degrees of freedom in the x, y, and z directions and a pressure-controlled dispenser). Due to its special rheological properties, the matrix can support the free printing of conductive paste in three-dimensional space ( Figure 1 ).
[0055] Preferably, the inner diameter of the printing nozzle in C can be selected to be 100 μm, 150 μm, 250 μm or 400 μm as required.
[0056] D. Curing and encapsulation of hydrogel electronic devices
[0057] The hydrogel electronic device printed in C can be cured and encapsulated under conditions such as ultraviolet light or heating according to the type of initiator to form a hydrogel electronic device with good stretchability and elasticity.
[0058] Preferably, the thermal initiator is ammonium persulfate (APS), the heating temperature is 60°C, and the heating time is 1h. Curing should be carried out in a high humidity and oxygen-free environment as much as possible; the photoinitiator can be Igracure2959 with good water solubility and low toxicity, and the ultraviolet light intensity is 50mW / cm 2 , time is 1h.
[0059] The following examples are used to illustrate the present invention, but are not intended to limit the scope of the present invention. Unless otherwise specified, the technical means used in the examples are conventional means well known to those skilled in the art, and the raw materials used are all commercially available products.
[0060] The planetary stirrer (model ARE-310) used in the following examples was purchased from Thinky (Japan).
[0061] The 3D printer is a 3-axis high-precision direct writing printer built by the laboratory, equipped with a glue dispenser (model Performus V, purchased from Nordson EFD Inc., USA).
[0062] Example 1 Fabrication of Hydrogel Electronic Strain Sensor
[0063] The following steps are involved:
[0064] A. Dissolve acrylamide (6.06 g) and sodium alginate (0.75 g) in deionized water (41.2 g) at 45°C with magnetic stirring to obtain a transparent viscous solution. After the solution is cooled to room temperature of 25°C, add crosslinker MBAA (2.496 mL, 2 mg / mL aqueous solution), initiator APS (181.8 mg), and EDTA-CaCl2 aqueous solution (0.25 M, pH 8-9). After all of them are dissolved, add GDL (0.6 g), and after it is dissolved, seal the resulting viscous solution and store it in a refrigerator at 4°C for 12 hours to form a calcium alginate gel.
[0065] B. Use a grinder to crush the gel obtained in step A into coarse gel particles, and then use a 10mL syringe and a syringe filter with a pore size of 20μm to filter the coarse gel particles into fine gel particles, and use a Thinky planetary mixer to degas them (2200rpm, until there are no bubbles) to obtain a uniform embedded 3D printing matrix gel, which is stored in a 4°C refrigerator.
[0066] C. PVP (specification K30, 44000-54000Da, 50mg, 40%wt aqueous solution), glycerol (50mg) and silver flakes (0.5g, 1.0g and 1.5g) with a size of 5μm were added to the matrix gel obtained in step B (1g), and mixed using a Thinky planetary mixer (2000rpm, 1.5min, 3 times, temperature not higher than 25°C). The resulting material was loaded into a 3mL barrel and centrifuged at 2500g for 10min to obtain a printable conductive paste. The temperature must not exceed 25°C room temperature during the entire process. The conductivity of the cured conductive paste was measured using a Hall effect meter and the Van der Pauw method. For the pastes with 0.5g, 1.0g and 1.5g of silver flakes added, the results were 2.1×10 1 S / cm, 4.0×10 2 S / cm and 1.4×10 3 S / cm. A slurry with a silver flake mass of 1.5 g was selected for subsequent printing.
[0067] D. Place the matrix gel obtained in step B into a 30mm×10mm×2.5mm mold, use a direct writing 3D printer to extrude and print the conductive paste selected in step C into the matrix gel, then cover the mold containing the matrix with a cover glass, and place it in a high humidity environment and heat it at 60°C for 1h to solidify it to obtain a hydrogel strain sensor. The printed device in this embodiment is a linear strain sensor with exposed conductive interfaces at both ends, with a line width of 250μm. When printing the exposed conductive interface, the needle is pressed against the bottom surface of the mold to extrude the conductive paste. The G code simulation diagram and the actual diagram are shown in the figure. Figure 4 (a) shown.
[0068] E. Using a desktop tensile tester, the hydrogel strain sensor obtained in step D is subjected to resistance-strain test and cyclic stretch test, such as Figure 4 (b) The results show that the sensor can withstand 1000% strain before damage, and its resistance increase ratio is approximately linearly related to the strain; in addition, the sensor shows good stability under 300% cyclic strain. The test results show that the hydrogel strain sensor prepared by this method and supporting materials has the potential to be used as a biological strain sensor and flexible electronics.
[0069] Figure 4 (c) is the resistance change rate-strain relationship diagram of the hydrogel strain sensor.
[0070] Figure 4 (d) is the resistance change rate-strain relationship diagram of the hydrogel strain sensor under 300% strain cycle.
[0071] Example 2 Fabrication of hydrogel inductor / antenna
[0072] The following steps are involved:
[0073] A. Material preparation is the same as in Example 1.
[0074] B. Place the matrix gel obtained in step A into a mold of suitable size, use a direct writing 3D printer to extrude and print the conductive paste into the matrix gel, then cover the mold containing the matrix with a cover glass, and place it in a high humidity environment and heat it at 60°C for 1 hour to solidify it to obtain a hydrogel strain sensor. The printed device in this embodiment is a series of spiral inductors with exposed conductive interfaces at both ends of different turns, and a solenoid wireless power supply antenna connected to a light emitting diode (LED). The G code simulation diagram and the actual diagram are shown in the figure. Figure 5 As shown in (a,b,d,e).
[0075] C. The manufactured inductance value was measured using an LCR bridge at 1V and 200kHz. The inductance value was compared with the inductance value obtained by simulation using Comsol software. The results showed that the two values were close to each other. Figure 5 (c) as shown.
[0076] D. Using the RF transmitting coil to give the antenna-LED device function, the results show that the printed antenna can make the 1206 model red LED work normally and emit light, such as Figure 5 (f) as shown.
[0077] Although the present invention has been described in detail above with general descriptions and specific embodiments, it is obvious to those skilled in the art that some modifications or improvements can be made based on the present invention. Therefore, these modifications or improvements made without departing from the spirit of the present invention all fall within the scope of protection claimed by the present invention.
Claims
1. A method for manufacturing a 3D printed hydrogel electronic device, characterized in that: The hydrogel matrix material is loaded into a mold with a certain shape, the conductive material is printed in the hydrogel matrix material according to a preset program using a 3D printer, and then cured under ultraviolet light or heating conditions to obtain a hydrogel electronic device with good stretchability and elasticity; The hydrogel matrix material is obtained by dissolving an ionically crosslinkable polymer compound, a free radical polymerizable monomer, a crosslinking agent and an initiator in deionized water, then introducing metal ions to cause the polymer compound to undergo ion crosslinking, and breaking the resulting gel into micronized gel particles; Wherein, the initiator is a thermal initiator or a photoinitiator; The ion-crosslinkable polymer compound is selected from sodium alginate, chitosan, and hyaluronic acid; The free radical polymerizable monomer is selected from acrylamide and polyethylene glycol diacrylate; The cross-linking agent is N,N-methylene acrylamide; The initiator is ammonium persulfate; The metal ion is a calcium ion; The preparation method of the hydrogel matrix material comprises: (1) dissolving an ionically crosslinkable polymer compound and a free radical polymerizable monomer in deionized water by magnetic stirring under heating conditions to obtain a transparent viscous solution; (2) cooling the viscous solution obtained in step (1) to below 25° C., adding a crosslinking agent, an initiator, and an ethylenediaminetetraacetic acid chelate of a metal ion, and stirring to dissolve the mixture; (3) adding D-gluconolactone to the solution obtained in step (2), stirring to dissolve it, and refrigerating the resulting solution overnight to form an ion-crosslinked gel; (4) mechanically crushing the ion cross-linked gel obtained in step (3) into coarse gel particles, filtering the coarse gel particles into fine gel particles using a syringe and a filter, and degassing the particles using a planetary mixer to obtain a hydrogel matrix material that can be used for embedded 3D printing; The conductive material is prepared by mixing the hydrogel matrix material with a polyvinyl pyrrolidone aqueous solution, glycerol and micron silver flakes using a planetary mixer, and then transferring the mixture to a barrel for centrifugal degassing to obtain a conductive material that can be used for 3D printing; The size of micronized silver flakes is 2-10 μm; The centrifugation conditions were: 18°C, 2000-2500g for 10 min.
2. The method according to claim 1, characterized in that The pore size of the syringe and filter used in step (4) is 20-50 μm.
3. The method according to claim 1, characterized in that The conductive material is characterized in that the conductive material is prepared by mixing a hydrogel matrix material with a 40%wt polyvinyl pyrrolidone aqueous solution, glycerol and micron silver flakes by a planetary stirrer, and then transferring the mixture to a barrel for centrifugal degassing to obtain a conductive material that can be used for 3D printing; The mass ratio of the hydrogel matrix material, 40%wt polyvinyl pyrrolidone aqueous solution, glycerol and micronized silver flakes is 1:(0.02-0.1):(0.05-0.1):(0.5-1.5); The molecular weight of polyvinylpyrrolidone is 44000-54000Da; The size of micronized silver flakes is 2-10 μm; The centrifugation conditions were: 18°C, 2000-2500 g for 10 min; The preparation method of the hydrogel matrix material comprises: 1) dissolving acrylamide and sodium alginate in deionized water under heating conditions by magnetic stirring to obtain a transparent viscous solution; 2) Cooling the viscous solution obtained in step 1) to below 25° C., adding N,N-methylene acrylamide aqueous solution and ammonium persulfate, and then adding 0.25M EDTA-CaCl2 aqueous solution at pH 8-9, stirring to dissolve; 3) adding D-gluconolactone to the solution obtained in step 2), stirring to dissolve it, and refrigerating the obtained solution overnight to form a calcium alginate gel; 4) using a grinder to mechanically crush the calcium alginate gel obtained in step 3) into coarse gel particles, then using a syringe and a filter to filter the coarse gel particles into fine gel particles, and using a planetary mixer to degas the fine gel particles to obtain a hydrogel matrix material; In step 1), the mass ratio of sodium alginate, acrylamide and deionized water is (0.6-1.4):(6-10):55; In step 2), the mass ratio of acrylamide, N,N-methylene acrylamide and ammonium persulfate is 1:(0.00082-0.04):(0.01-0.05); The mass ratio of sodium alginate, EDTA-CaCl2 aqueous solution and D-gluconolactone is 1:(1.3-3.0):(0.48-1.12).
4. The method according to claim 3, characterized in that: The pore size of the syringe and filter used in step 4) is 20-50 μm.
Citation Information
Patent Citations
Stretchable microelectronic device taking hydrogel as substrate and preparation method
CN110970232A
Flexible force tactile sensor based on transparent biomaterial, sensitive element and preparation methods of flexible force tactile sensor and sensitive element
CN107941386A
Full-supporting hydrogel 3D printing method based on constant rheological characteristic
CN110103463A